2020
DOI: 10.1200/po.19.00335
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Validation Study to Implement Plasma Epidermal Growth Factor Receptor T790M Testing in Clinical Laboratories

Abstract: PURPOSE Plasma detection of EGFR T790M mutations is an emerging alternative to tumor rebiopsy in acquired epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor resistance. Validation of analytical sensitivity and clinical utility is required before routine diagnostic use in clinical laboratories. PATIENTS AND METHODS Sixty-three patients with advanced EGFR-mutant lung cancer at 7 Canadian centers, who were being screened for the ASTRIS trial (ClinicalTrials.gov identifier: NCT02474355 ), participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 25 publications
(24 reference statements)
0
15
0
Order By: Relevance
“…Although such platforms offer broad-based testing of known and unknown variants, non-NGS PCR-based ctDNA assays (either as a single gene or multiplexed), known to be highly sensitive for detecting a select few targetable alterations, may still offer a lower-cost alternative in resource-limited settings. However, liquid biopsy has been shown to help to avoid repeat tissue biopsy in patients with small samples, increase the identification of patients with actionable alterations, which may offset costs and offer short TAT [26,50]. Furthermore, it is expected that the costs of liquid biopsy technology will decrease over time, and the use of non-commercial assays or price negotiation may make this strategy more affordable in future.…”
Section: Discussionmentioning
confidence: 99%
“…Although such platforms offer broad-based testing of known and unknown variants, non-NGS PCR-based ctDNA assays (either as a single gene or multiplexed), known to be highly sensitive for detecting a select few targetable alterations, may still offer a lower-cost alternative in resource-limited settings. However, liquid biopsy has been shown to help to avoid repeat tissue biopsy in patients with small samples, increase the identification of patients with actionable alterations, which may offset costs and offer short TAT [26,50]. Furthermore, it is expected that the costs of liquid biopsy technology will decrease over time, and the use of non-commercial assays or price negotiation may make this strategy more affordable in future.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the clinical utility of T790M detection in ctDNA using various platforms leading to implementation of liquid biopsy in this clinical setting. For patients with a plasma T790M-negative result, reflex tissue biopsy and tissue genotyping is recommended [ 56 58 ]. Osimertinib, a third-generation EGFR inhibitor, has now moved to the first-line setting as treatment for patients with advanced EGFR mutant NSCLC [ 24 ].…”
Section: Current Applicationsmentioning
confidence: 99%
“…In a Canadian validation study of plasma EGFR T790M testing, plasma testing showed more T790M‐positive results (62%) than tumor biopsy alone (49%), with 75% sensitivity using highly sensitive methods such as ddPCR, next‐generation sequencing, and RT‐PCR 26 . Therefore, ctDNA EGFR analysis could be used in clinical practice as a routine diagnostic tool in a post‐EGFR‐TKI setting and for initial screening at diagnosis.…”
Section: Discussionmentioning
confidence: 99%